Water uptake by organic aerosol and its influence on gas/particle partitioning of secondary organic aerosol in the United States. (March 2016) - Jathar, Shantanu H.; Mahmud, Abdullah; Barsanti, Kelley C.; Asher, William E.; Pankow, James F.; Kleeman, Michael J.
Abstract: Organic aerosol (OA) is at least partly hygroscopic, i.e., water partitions into the organic phase to a degree determined by the relative humidity (RH), the organic chemical composition, and the particle size. This organic-phase water increases the aerosol mass and provides a larger absorbing matrix while decreasing its mean molecular weight, which can encourage additional condensation of semi-volatile organic compounds. Most regional and global atmospheric models account for water uptake by inorganic salts but do not explicitly account for organic-phase water and its subsequent impact on gas/particle partitioning of semi-volatile OA. In this work, we incorporated the organic-phase water model described byPankow et al. (2015) into the UCD/CIT air quality model to simulate water uptake by OA and assessed its influence on total OA mass concentrations. The model was run for one summer month over two distinct regions: South Coast Air Basin (SoCAB) surrounding Los Angeles, California and the eastern United States (US). In SoCAB where the OA was dominated by non-hygroscopic primary OA (POA), there was very little organic-phase water uptake (0.1–0.2 μg m −3 ) and consequently very little enhancement (or growth) in total OA concentrations (OA + organic-phase water): a 3% increase in total OA mass was predicted for a 0.1 increase in relative humidity. In contrast, in the eastern US where secondary OA (SOA) from biogenic sources dominated the OA, substantial organic-phase water uptake and enhancement in total OA concentrations was predicted, even in urban locations. On average, the model predicted a 20% growth in total OA mass for a 0.1 increase in relative humidity; the growth was equivalent to a 250 nm particle with a hygroscopicity parameter (κ) of 0.15. Further, for the same relative humidity, the exact extent of organic-phase water uptake and total OA enhancement was found to be dependent on the particle mixing state. When the source-oriented mixing state of aerosols was considered, generally, less organic-phase water uptake was predicted than when simple internal mixing approximations were made. Overall, the results indicated that organic-phase water can significantly influence predicted total OA concentrations under certain conditions. Regional models applied in areas with high humidity and significant SOA formation should include calculations for organic-phase water in order to capture this effect. Highlights: Organic-phase water is predicted in eastern US and California using the same model. Organic-phase water enhances SOA formation in the eastern US. Organic-phase water has small effect on SOA formation in California. Different behavior is driven by regional emissions profiles. Particle mixing state changes the impact of organic-phase water.